Arranjos estéticos e produção de moda nos figurinos em cinema como formato de publicidade das marcas de luxo - Del-Vechio , Roberta (2018)
Fashion and costume in cinema can build relations and intersections. When the narrative establishes these relations, in some contexts, the Costume Designer composes the costume with luxury brands. Working the luxury universe is by itself investigate the production of visuality, the design articulation with the brand image, the production of a desire world, the construction of social predicates. The luxury incorporated into the costume increases the power of enunciation, an advertising enunciation, because when using luxury brands in the characters costume, the image of the brands with their respective identity proposals is spread. Even though in fashion production the name of the brand is not declared as in the marketed message in media space (as product placement actions), certainly, the propagation of the luxury brands identity by the costume brings identity to characters, visibility for the brands and for cinematographic production. The thesis that is defended is that the costume in cinema, when composed by aesthetic arrangements and fashion production, using luxury brands, produces a certain fashion image, has enunciative potentiality and is revealed, in this context, in an advertising format with different characteristics, in which the luxury brand in the costume composition is recognized by its design, by its identity attribute, thus conceiving the term Luxury brand costume placement. The research is characterized as qualitative, exploratory, with the use of multiple cases studies and aims to arouse the conception that when articulating luxury brands in the aesthetic arrangements and fashion production of the costumes in movies, they are configured as advertising. In order to reach the study objective, the empirical corpus contains the investigation of a selection made in cinematographic production (movies produced from 2013 to 2017), whose costumes present esthetic arrangements and fashion production with luxury brands - not characterized as product placement. The guiding thread is the theories that study the production of meaning (Eric Landowsky) the Enunciation (José Luiz Fiorin) and the Advertising Mediatic Enunciation (Ivan Barbosa and Eneus Trindade). However, in approaching the Costume in Cinema (which includes clothing and body), the thesis relates two distinct fields, Advertising and Luxury Fashion - the theories that contribute to reflect about these two instances are also approached to strengthen the arguments bases of the proposed thesis. With the results, it was verified that the cinema costume articulated with the luxury brands, with the body and with the performance, creates a hybrid, syncretic discourse in an advertising format with peculiar characteristics, whose aesthetics and lifestyles of the characters are projected by a performance staged (not posed) in which the fashion image generated by the costume enunciates a discourse that has its marks, its wiles, linked to recognition codes of the luxury brands and, consequently, there is a Placement, a appearance of the luxury brand articulated to the costume.